CURRENT STAGE OF DIPLOMATIC RELATIONS BETWEEN TURKEY AND UZBEKISTAN (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
This article provides a scholarly analysis of the content, driving factors, and institutional characteristics of diplomatic relations between Turkey and Uzbekistan at the current stage. The study highlights the intensification of political dialogue between the two states, the formation of a strategic partnership, and the strengthening of diplomatic trust mechanisms as key outcomes. Particular attention is paid to the role of cultural-humanitarian and public diplomacy, as well as the significance of cooperation within international and regional organizations. Based on contemporary theories of international relations, the article formulates conclusions and identifies the future prospects of Turkey–Uzbekistan diplomatic relations.